2020
DOI: 10.3389/fimmu.2020.01369
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell Uses for Acute Kidney Injury—Current Available Data and Future Perspectives: A Mini-Review

Abstract: There is growing evidence concerning the potential use of mesenchymal stromal cells (MSCs) for different tissue injuries. Initially, the intended physiological use of MSCs was due to their ability to differentiate and replace damaged cells. However, MSCs have multiple effects, including being able to significantly modulate immunological responses. MSCs are currently being tested for neurodegenerative diseases, graft vs. host disease, kidney injury, and other chronic unremitting tissue damage. Using MSCs in acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…As noted above, AKI is usually associated with disorders and abnormal activation of the immune system, which can in turn be affected by treatment with MSCs and their EVs, suggesting that utilizing and modifying EVs to regulate the immunomicroenvironment might be an efficient and effective therapeutic approach for AKI (100)(101)(102)(103)(104)(105)(106). Although some researchers have reported that MSCs and MSC-EVs can affect the immune function and immune microenvironment in AKI both in vitro and in vivo, the findings have been inconsistent (107).…”
Section: Evs Participate In the Immune Regulation Of Mscs In Akimentioning
confidence: 99%
“…As noted above, AKI is usually associated with disorders and abnormal activation of the immune system, which can in turn be affected by treatment with MSCs and their EVs, suggesting that utilizing and modifying EVs to regulate the immunomicroenvironment might be an efficient and effective therapeutic approach for AKI (100)(101)(102)(103)(104)(105)(106). Although some researchers have reported that MSCs and MSC-EVs can affect the immune function and immune microenvironment in AKI both in vitro and in vivo, the findings have been inconsistent (107).…”
Section: Evs Participate In the Immune Regulation Of Mscs In Akimentioning
confidence: 99%
“…Clinical trials with MSC administration in patients with AKI or sepsis-associated AKI, chronic kidney disease or diabetic nephropathy has been limited to a small number of early phase clinical trials. Overall, MSC demonstrated good safety and tolerability, however only modest alterations in plasma cytokine profiles were observed, without a clear signal of improved outcome for MSC-treated patients [ [156] , [157] , [158] ].…”
Section: Mscs-based Therapies For Multiple Organs Affected By Covid-1mentioning
confidence: 99%
“…Renal tubular epithelial cell (RTEC) injury due to ischemia-reperfusion injury (IRI), nephrotoxicity and other causes lead to a rapid decline in renal function and over-activated inflammatory immune response. If the inflammatory damage to RTEC was not controlled timely, a continuous renal injury would result in renal fibrosis and failure (1)(2)(3). Unfortunately, current pharmacological interventions have failed to prevent intrarenal inflammatory cascade.…”
Section: Introductionmentioning
confidence: 99%